Directional Potassium Transport through a Unimolecular Peptide Channel. (18th October 2016) - Su, Ge; Zhang, Min; Si, Wen; Li, Zhan‐Ting; Hou, Jun‐Li
Abstract: Three unimolecular peptide channels have been designed and prepared by using the β‐helical conformation of gramicidin A (gA). The new peptides bear one to three NH3 + groups at the N‐end and one to three CO2 − groups at the C‐end. These zwitterionic peptides were inserted into lipid bilayers in an orientation‐selective manner. Conductance experiments on planar lipid bilayers showed that this orientation bias could lead to observable directional K + transport under multi‐channel conditions. This directional transport behavior can further cause the generation of a current across a planar bilayer without applying a voltage. More importantly, in vesicles with identical external and internal KCl concentrations, the channels can pump K + across the lipid bilayer and cause a membrane potential.